2023
DOI: 10.22575/interventionalradiology.2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Radiofrequency Ablation Combined with Transarterial Chemoembolization Using Degradable Starch Microsphere Mixed with Mitomycin C for the Treatment of Non-hepatocellular Carcinoma Malignant Liver Tumors

Abstract: Purpose: To retrospectively evaluate the outcomes of radiofrequency ablation combined with transarterial chemoembolization using degradable starch microspheres for non-hepatocellular carcinoma malignant liver tumors. Material and Methods: A total of 15 patients (13 men, 2 women; median age, 67 years) who underwent radiofrequency ablation immediately after transarterial chemoembolization using degradable starch microspheres for liver tumors between July 2011 and September 2020 were included in this study. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Combining radiofrequency ablation (RFA) with DMS-TACE has been described as a promising approach for the treatment of CRLM [38], and more recently, it has been explored for other non-HCC primary or metastatic malignant liver lesions [39]. This combined therapy offers the advantages of both modalities, while studies have demonstrated encouraging results, with high rates of tumor control and the possibility of managing local tumor progression with repeated sessions, as well as prolonged overall survival [39]. Moreover, the synergistic effects of ablation and TACE may facilitate complete tumor eradication and reduce the likelihood of tumor recurrence, particularly in cases where lesions are larger or located in challenging anatomical locations [40,41].…”
Section: Dms-tace Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining radiofrequency ablation (RFA) with DMS-TACE has been described as a promising approach for the treatment of CRLM [38], and more recently, it has been explored for other non-HCC primary or metastatic malignant liver lesions [39]. This combined therapy offers the advantages of both modalities, while studies have demonstrated encouraging results, with high rates of tumor control and the possibility of managing local tumor progression with repeated sessions, as well as prolonged overall survival [39]. Moreover, the synergistic effects of ablation and TACE may facilitate complete tumor eradication and reduce the likelihood of tumor recurrence, particularly in cases where lesions are larger or located in challenging anatomical locations [40,41].…”
Section: Dms-tace Proceduresmentioning
confidence: 99%
“…Moreover, the synergistic effects of ablation and TACE may facilitate complete tumor eradication and reduce the likelihood of tumor recurrence, particularly in cases where lesions are larger or located in challenging anatomical locations [40,41]. Additionally, the degradable nature of DMS allows for repeated treatment if necessary, enabling the adaptation of therapeutic approaches based on tumor response and disease progression [39], exemplified in the case illustrated in Figure 1. (c) Initial DSA prior to the 2nd DMS-TACE session (1 month after the 1st session), demonstrating complete viability of the right-lobe arterial supply, including the feeding vessels of the target HCC lesions.…”
Section: Dms-tace Proceduresmentioning
confidence: 99%